Episodic Reversal of Autumn Ice Advance Caused by Release of Ocean Heat in the Beaufort Sea. Issue 5 (6th May 2018) - Smith, Madison; Stammerjohn, Sharon; Persson, Ola; Rainville, Luc; Liu, Guoqiang; Perrie, William; Robertson, Robin; Jackson, Jennifer; Thomson, Jim
Abstract: High‐resolution measurements of the air‐ice‐ocean system during an October 2015 event in the Beaufort Sea demonstrate how stored ocean heat can be released to temporarily reverse seasonal ice advance. Strong on‐ice winds over a vast fetch caused mixing and release of heat from the upper ocean. This heat was sufficient to melt large areas of thin, newly formed pancake ice; an average of 10 MJ/m 2 was lost from the upper ocean in the study area, resulting in ∼3–5 cm pancake sea ice melt. Heat and salt budgets create a consistent picture of the evolving air‐ice‐ocean system during this event, in both a fixed and ice‐following (Lagrangian) reference frame. The heat lost from the upper ocean is large compared with prior observations of ocean heat flux under thick, multiyear Arctic sea ice. In contrast to prior studies, where almost all heat lost goes into ice melt, a significant portion of the ocean heat released in this event goes directly to the atmosphere, while the remainder (∼30–40%) goes into melting sea ice. The magnitude of ocean mixing during this event may have been enhanced by large surface waves, reaching nearly 5 m at the peak, which are becoming increasingly common in the autumn Arctic Ocean. The wave effects are explored by comparing the air‐ice‐ocean evolution observed at short and long fetches, and a common scaling for Langmuir turbulence. After the event, the ocean mixed layer was deeper and cooler, and autumn ice formation resumed. Plain Language Summary: As Arctic Ocean temperatures drop below freezing in the autumn, sea ice begins to form, sealing off the ocean below. The ice's southward advance throughout autumn is not linear, however, as storm events may act to pause its progression. We observed a 4 day storm event in the western Arctic Ocean in October 2015 with strong winds (up to 20 m/s) and large waves (over 4 m). As a result, heat from the upper ocean was mixed to the surface, melting approximately 5 cm thick ice over a vast area. This event temporarily reversed autumn ice advance and resulted in a thinner winter ice cover. This study is the first to document autumn melt of sea ice by ocean heat in the thin, new ice that increasingly dominates in the Arctic Ocean. The magnitude of the heat lost is likely related to the large surface waves during this event that result from lower sea ice cover. These results highlight the importance of air‐sea interactions in current and future Arctic sea ice cover. Key Points: A Beaufort Sea autumn storm released a large amount of upper ocean heat, melting thin, new sea ice Heat release was larger than in prior studies under multiyear ice, with a greater role by atmospheric heat fluxes The forcing conditions in this event are related to the changing wave climate in the western Arctic Ocean